2013
DOI: 10.2319/021313-130.1
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis of mandibular prognathism in Korean orthognathic surgery patients and their families

Abstract: Objective: To investigate the existence of genetic influences on the incidence of mandibular prognathism (MP) in Korean Class III patients. Materials and Methods: The probands consisted of 100 Class III patients with MP (51 men and 49 women; mean age, 22.1 6 5.2 years; SNA, 81.2u 6 3.2u; SNB, 84.1u 6 3.9u) who underwent orthognathic surgery. Using three-generation pedigree charts, questionnaires, and clinical examinations, general information and information regarding MP for a total of 3777 relatives of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[4] However, no significant association was found between variants of FGF23 and MP in this case-control association study. These suggests us that the genetic mechanisms of MP are complex, [37] the main effects of the identified variants are considered to confer relatively small increments in risk, and explain only a small proportion of the heritability.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[4] However, no significant association was found between variants of FGF23 and MP in this case-control association study. These suggests us that the genetic mechanisms of MP are complex, [37] the main effects of the identified variants are considered to confer relatively small increments in risk, and explain only a small proportion of the heritability.…”
Section: Discussionmentioning
confidence: 74%
“…Both monogenic (dominant or recessive) and polygenic inheritance manners have been suggested by different studies. [24] With the evidence accumulated, it is now accepted by most researchers that MP is a polygenic disorder with both environmental and genetic risk factors attributed to its etiology. [1,5,6] Although genetic linkage analysis and association studies have identified many genes and loci associated with MP, [1,717] the genes underlying the risk of MP in the general population remain elusive, leaving some impetus to search for new candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…Interindividual variability was statistically significant for eight (Co‐Gn, Co‐A, ANS‐Me, SNA, SNB, ArGoMe, PP‐MP, NSBa) out of ten variables considered. Variability can be due to a summation of minor effects from a variety of different genes and/or from the influence of epigenetic factors …”
Section: Discussionmentioning
confidence: 99%
“…28 In another study, the heredity pattern was found to be autosomal dominant with 0.70 incomplete penetrance. 25 Ko and colleagues 29 examined 100 Korean subjects with MP and concluded that both genetic and environmental factors are responsible for susceptibility to MP in Korean patients with Class III rather than Mendelian inheritance.…”
Section: Discussionmentioning
confidence: 99%